Mechanism and kinetics of early transition metal hydrides, oxides, and chlorides to enhance hydrogen release and uptake properties of MgH2. (22nd April 2015) - Korablov, Dmytro; Nielsen, Thomas K.; Besenbacher, Flemming; Jensen, Torben R.
Abstract : Selected hydrides (TiH2, ZrH2 ), chlorides (VCl3, ScCl3 ) or oxides (V2 O5 ) utilized as additives facilitating hydrogen release and uptake for magnesium hydride were investigated using mechano-chemical treatment and in-situ synchrotron radiation powder X-ray diffraction studies. The fastest hydrogen desorption and absorption kinetics for MgH2 was observed for a sample with 5 mol% V2 O5 at 320 °C. Additional activation of the system (2 cycles, vacuum/ p (H2 ) ~150 bar, 450 °C) leads to significant improvement of the kinetics even at lower temperatures, 270 °C. The observed prolific effect is achieved through the full reduction of vanadium oxides and formation of an efficient vanadium catalyst as nanoparticles and possibly interfacial effects in the MgO/Mg/MgH2 /V system introduced during cycling hydrogen release and uptake in hydrogen/dynamic vacuum at 450 °C. Nanostructuring as well as hydrogen permeability via vanadium nanoparticles may improve kinetics and reduce the apparent activation energy for hydrogen release. Thus, the enhancement of hydrogen release/uptake in the MgH2 owe to " in situ " formation of vanadium nanoparticles by reduction of V2 O5 .